Production of Formosa papaya seedlings irrigated with wastewater and application of biostimulant - Moura, Elias Ariel; Oliveira, Luana Mendes; Mendonça, Vander; Mendonça, Luciana Medeiros de Freitas; Figueiredo, Francisco Romário Andrade; Celedônio, Wilma Freitas; Cardoso, Anna Paula Marques (Comunicata Scientiae, 2020)
Papaya (Carica papaya L.) is one of the leading fruit trees in Brazil, mainly in the Northeast region. However, some regions suffer from water scarcity, making wastewater reuse a viable alternative for crop production. Also, biostimulants may be used to maximize papaya growth and development. Thus, this work aimed to evaluate the use of Acadian® biostimulant in the growth of Formosa papaya seedlings irrigated with different concentrations of fish-farming wastewater. The experiment was block randomized in a 2 x 5 factorial scheme, use and non-use of biostimulant and five concentrations of wastewater (0, 10, 20, 30, and 40%) diluted in potable water, with four replicates. Qualitative data were compared by t-test at 5% probability, and quantitative data were submitted to regression analysis. Results showed that high concentrations of wastewater negatively affect the production of Formosa papaya seedlings. Acadian® negatively influences plant height, number of leaves, and the ratio between shoot and root. However, the seaweed biostimulant positively influenced the chlorophyll content index.